Archaeology and Emerging Kabikolan [Book review] - Avellana, Reynaldo R. (2016)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/5497/4931
Keywords: Books -- Reviews; Archaeology; Bicol Region